A Comparative Study of Modern Theatrical Technicalities in The Glass Menagerie and The Cherry Orchard (Raparin Journal of Humanities (RJH), 2021)
The nineteenth Century produced some of the most complex plays that today represent modern theatrical technicalities that differed in several ways from twentieth Century plays. In the twentieth Century, Tennessee Williams was acknowledged for the diversity of genres he covered in his plays, most of which focused on the dark aspects of human experience, which lent significant technicalities to his plays, most notably, The Glass Menagerie. Similarly, Anton Chekhov is a nineteenth Century playwright who developed plays that introduced several theatrical technicalities. He was renowned for portraying realism, a feature that characterised 19th Century theatre. Chekhov’s The Cherry Orchard is a play considered the landmark of modern theatrical technicalities.This study explores three ways in which Williams and Chekhov made The Glass Menagerie and Cherry Orchard respectively as landmarks of theatrical technicalities, i.e., the multiplicity of genres, effective use of indirect action and irony as theatrical conventions, and the integration and portrayal of nineteenth Century and twentieth Century realism. The research finds that while Williams employs a multiplicity of genres and the use of irony as the ideal theatrical conventions, Chekhov integrates all three elements to create modern theatrical technicalities that not only influence the audience's perception of the characters but also the playwright’s intention.This study is important for both undergraduate and postgraduate readers as it can enrich a reader’s thinking about different theatrical techniques and conventions used in both plays.